Headmaster Academic Supervision Management in Improving the Professional Competence of Primary School Teachers in Cianjur - Sarah Sarah; Helmawati Helmawati (Journal of Science and Education (JSE), 2026)
The quality of elementary education is largely determined by teachers’ professional competence; however, many elementary school teachers still face challenges in mastering subject matter, managing classrooms, and utilizing instructional technology. One strategic effort to address these issues is through the principals’ management of academic supervision that is well-planned, systematic, and sustainable. This study aims to analyze the management of academic supervision by principals in improving teachers’ professional competence at SDN Cikareo and SDN Margasari, Cidaun District, Cianjur Regency. The research employed a qualitative approach with a case study design. Data were collected through observations, in-depth interviews, and document analysis, then analyzed using data reduction, data display, and verification with triangulation. The findings revealed that at SDN Cikareo, academic supervision was scheduled and implemented according to the program, but the follow-up stage after observation remained largely administrative. In contrast, at SDN Margasari, academic supervision was more flexible but less structured and poorly documented. The main obstacles encountered included limited time, low teacher motivation, and a school culture that had not fully supported supervision. Solutions undertaken by principals included careful planning, dialogic supervision with reflective feedback, and fostering a positive school culture. The study concludes that principals’ academic supervision management plays a strategic role in enhancing teachers’ professional competence, particularly in subject mastery, pedagogical skills, and classroom management, which ultimately contributes positively to the quality of learning in elementary schools.